2020
DOI: 10.1108/jmd-12-2019-0503
|View full text |Cite
|
Sign up to set email alerts
|

A model of perceptions of politics: antecedents and outcomes

Abstract: PurposeThe purpose of this paper is to examine the influence of one personal variable (locus of control) and two relationship variables (leader-member exchange and co-worker cooperation) on perceptions of organizational politics in Lebanese small and medium-sized enterprises (SMEs).Design/methodology/approachSurvey data was collected from 300 Lebanese employees from different SMEs located between Tripoli and Beirut.FindingsResults of regression analysis indicated that all the three variables were significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Thus, H1 is supported and the regression equation could be as shown in figure 1. This result was confirmed by other studies (Al Jisr et al, 2020;Arefin et al, 2020;De Clercq et al, 2021). The reason could be that perceived political behavior in the workplace represents a stressor to employees.…”
Section: Hypotheses Testingsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, H1 is supported and the regression equation could be as shown in figure 1. This result was confirmed by other studies (Al Jisr et al, 2020;Arefin et al, 2020;De Clercq et al, 2021). The reason could be that perceived political behavior in the workplace represents a stressor to employees.…”
Section: Hypotheses Testingsupporting
confidence: 86%
“…There are many antecedents have been found to have a negative relationship with turnover intention such as; engagement (Agarwal, 2016), organizational justice (George & Wallio, 2017), fellow workers' warmth and competence (Abd El-Aty & Deraz, 2018), job satisfaction (Chan & James, 2020;Samengon et al, 2020), organizational commitment (Samengon et al, 2020), trust in supervisor, and on-the-job embeddedness (Ampofo & Karatepe, 2021). On the other hand, other factors have been found to have positive relationship with turnover intention such as; interpersonal conflict (Haq, 2011), work-leisure conflict (Mansour & Tremblay, 2016), work-family conflict (Chen et al, 2018), job burnout (Back et al, 2020;Wen, Zhou, Hu & Zhang, 2020), perception of organizational politics and political behavior (Al Jisr et al, 2020;Arefin et al, 2020;De Clercq et al, 2021), job stress (Samengon et al, 2020;Wen et al, 2020), emotional labor (Back et al, 2020), and emotional exhaustion (Chan & James, 2020;Grobelna, 2021;Parray, Islam & Shah, 2022).…”
Section: Turnover Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research findings have established a link between leader-member exchange and POPs (e.g., Rosen et al, 2011;Williams et al, 2016;Al Jisr et al, 2020). The construct has been found to be negatively related to POPs where relationships are poor (Miller and Nicols, 2008;Ferris and Kacmar, 1992;Kacmar et al, 1999).…”
Section: Leader-member Exchangementioning
confidence: 99%
“…It has attracted increasing attention from scholars and practitioners in recent decades (Li et al, 2014;Ferris et al, 2019). Numerous studies have indicated that POP has a strong influence on work attitudes and behaviors, such as psychological strain, job satisfaction, turnover intentions, organizational citizenship behavior (OCB; Organ, 1988), and task performance (Chang et al, 2009;Al Jisr et al, 2020). Nevertheless, the study of POP's effect on voice behavior is underdeveloped.…”
Section: Introductionmentioning
confidence: 99%